The Influence of Teaching Materials, Reading Literacy, and Achievement Motivation on Learning Outcomes - Lilis Ismayani; Sumanti Sumanti; Hariki Fitrah (Universitas Lambung Mangkurat, 2025)
This study aims to analyze the influence of teaching materials, reading literacy, and achievement motivation on the geography learning outcomes of tenth-grade students at SMAN 1 Indrajaya. The research employed a quantitative approach with a descriptive design. A total of 103 students were selected as the sample using Slovin’s formula. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression. The results indicate that the three variables significantly affect learning outcomes, both simultaneously and partially, with a coefficient of determination of 0.728. Reading literacy has the most dominant influence (β = 0.375), followed by teaching materials (β = 0.343) and achievement motivation (β = 0.162). These findings highlight the critical role of reading literacy as the primary determinant of success in learning geography. This study contributes to existing research by presenting a comprehensive analytical model, emphasizing the need for learning strategies that prioritize literacy, contextual teaching materials, and motivation. The limitation of this study lies in the sample scope, which was restricted to a single school; therefore, further research with a broader sample is recommended.